1976
DOI: 10.1104/pp.57.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and Contraction of Mitochondria from Cold-hardened and Nonhardened Wheat and Rye Seedlings

Abstract: A comparison of mitochondria isolated from 2 and 24 C grown winter wheat (Triticum aestivum L.) and winter rye (Secak cereak L.) seedlings revealed no correlation between changes in swelling and contraction characteristics and extent of cold hardiness. The swelling response changed markedly due to growth at low temperature, but the change was similar for the four cultivars examined. The swelling response was also observed to change rapidly during aging of isolated mitochondria, either at 2 or 24 C. Spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Several investigators have suggested that cold hardening may in fact be related to an increase in membrane flexibility, at low temperatures (14,19). Membranes are relatively fragile components of cells, and may be injured by a variety of stress conditions (14).…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have suggested that cold hardening may in fact be related to an increase in membrane flexibility, at low temperatures (14,19). Membranes are relatively fragile components of cells, and may be injured by a variety of stress conditions (14).…”
Section: Resultsmentioning
confidence: 99%
“…Under certain conditions, it is believed that proton pumping can be exclusively linked to cation transport, forming a cycle whereby continual exchange of protons for cations such as Na + , K + and Ca 2+ outcompetes ATP synthesis for the electrochemical gradient established via substrate oxidation (Bernardi ; Pastore et al ). Analyses of isolated mitochondria incubated in saline conditions showed that certain ions accumulate within the mitochondrion at concentrations far higher than by diffusion alone (Lorimer & Miller ; Pomeroy ). Furthermore, ion accumulation is dependent upon the presence of respiratory substrates, but is not dependent upon ATP hydrolysis.…”
Section: Introductionmentioning
confidence: 99%